Application of Eco-enzyme for Hospital Wastewater Treatment at Short Contact Time - Lily Surayya Eka Putri; Arina Findo Sari; Cynthia Febri Antika; Cori Amelia Putri (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Organic solid waste management has become an important issue due to rapid population growth. Eco-enzyme (EE) is one of the many green technologies needed today to treat organic solid waste. The purpose of this study was to utilize EE to treat hospital wastewater with dilutions of 5, 10, and 15% with a contact time of 30 minutes, thus meeting the established wastewater quality standards (Regulation of the Kementerian Lingkungan Hidup No. 11/2025). The bio-physicochemical characteristics analyzed included BOD, COD, TSS, pH, and Escherichia coli count. The results showed a significant reduction in all bio-physicochemical characteristics and met the applicable quality standards. The effectiveness of pollutant reduction was very significant, reaching 93.67% for BOD, 97.85% for COD, and 89.71% for TSS, with 15% EE treatment. The reduction in E. coli numbers was also very significant, reaching 99.85%. Therefore, because EE products are simple, affordable, and environmentally friendly, they are recommended as biological products for hospital wastewater treatment.